(untitled) (Biological Sciences - PJSIR, 2022)
Zinc (Zn) deficiency is wide-spread in agricultural crops produced on alkaline calcareous soils of Pakistan. A greenhouse study was, therefore, undertaken on six soil series of rice area for evaluating the suitability of different extractants for extracting available zinc and to determine the critical soil Zn values for predicting rice response to Zn application. Zinc treatments were nil and 10 mg Zn kg" soil. Rice variety KS 282 was the test variety. Results revealed that DTPA extractable Zn in the soil had positive correlation with relative dry matter yield, tillers (in control pots), Zn concentration and its uptake in rice. Similarly, AB-DTPA extractable Zn was significantly correlated with the number of tillers/plants dry matter yield and Zn uptake in rice. Mehlich-3 extractable Zn had highly significant correlation with relative dry matter yield and Zn concentration in rice. Zinc extracted by HCI was significantly correlated with the number of tillers/plant and dry matter yield and it has highly significant correlation with Zn uptake in rice. Ammonium acetate extractable Zn was neither correlated with rice growth parameters nor with Zn concentration and its uptake in rice. Critical values ofZn determined were: DTPA, 0.99 mg Zn kg’: AB-DTPA, 1.22 mg Zn kg’: Mehlich-3, 2.47 mg Zn (dm ’)" and HCl, 0.34 mg Zn kg’ soil. The AB-DTPA procedure of monitoring Zn availability in soils is preferred since it is a multielement soil test.